Comments on the 2023 Draft Merger Guidelines: A Labor Market Perspective - David Berger; Thomas Hasenzagl; Kyle Herkenhoff; Simon Mongey; Eric A. Posner (Institute of Labor Economics (IZA), 2023)
The DOJ and FTC clarify the role of labor market power ("monopsony") in the 2023 draft merger guidelines. The draft states in Guideline 11 that the structural presumption threshold applies to labor market concentration, while also suggesting that a stricter threshold may be warranted in labor markets. The post-merger Herfindahl-Hirschman Index (HHI) that defines a highly concentrated market is 1800, which is lower, and so stricter, than the 2010 guidelines. We provide five comments on the draft guidelines based on our recent work Berger, Hasenzagl, Herkenhoff, Mongey, and Posner (2023). (1) Explicitly addressing monopsony in the draft guidelines is grounded in economic theory and empirical research. (2) Workers benefit from the lower threshold for highly concentrated markets. (3) The narrow nature of labor markets and high degree of monopsony power in the U.S. may warrant an even lower threshold. For example, merger simulations indicate that workers would benefit if the agencies lowered the HHI threshold further—to 1500 or 1000. (4) Worker welfare is central to the 2023 draft guidelines but the language is not always clear about this. The guidelines should make clear that degradations of "worker welfare" or "total compensation" indicate anticompetitive effects. (5) Dominant firms that can slow wage growth – but not freeze or cut wages – are subject to Guideline 7.
Keywords: J42; G34; K21; L4; 330; mergers; monopsony; labor market power; concentration